Pode um desejo imenso: homoerotismo na ficção de Frederico Lourenço - Félix, Maurício Dutra (2024)
Portuguese writer, translator, essayist and university professor, Frederico Lourenço released, in 2002, his first novel: Pode um desejo imenso, being awarded, the following year, with the Prémio Primeira Obra do P.E.N. Clube Português. The work narrates the internal and external romantic conflicts of the protagonist, university professor Nuno Galvão, during the moments preceding a colloquium on the Portuguese poet Luís de Camões, in the city of Lisbon, and those simultaneous to the event. In a game of metaphors and references to Greek culture, Nuno finds himself in love with his student and future master's advisor, Filipe Vaz, who, until the beginning of the plot, is in a relationship with another of the professor's students, Patrícia. While he comes into conflict with this forbidden desire, still considered taboo in today's society, the professor feels the repression of the colloquium organizers when they remove him from the opening of the event, because of the title of his conference: “Camões and D. António de Noronha: homoerotic echoes in Rimas”. Based on these aspects, this research project aims to analyze the references (both Greek and those from the poetry of Luís de Camões, a tutelary figure in Portuguese literature), and how these contribute to thinking about other possible ways of loving, outside the standards heteronormative. In other words, based on the analysis of the relationships established between the characters Nuno Galvão and Filipe Vaz, the work also aims to verify how homoerotic desire(s) arise from the clues left by Frederico Lourenço, as a possibility of expressing an immense desire within a sphere of possibility and realization.